The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/biof.1758
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: A regulator of the interplay between FoxO1, miR96, and miR215 signaling to diminish the growth, survival, and metastasis of murine adenocarcinoma

Abstract: Melatonin (Mel.), also known as the magic hormone, is a nocturnally secreted hormone orchestrates the clearance of free radicals that have been built up and cumulated during day. This study aims to detect the impact of pineal gland removal on the incidence of tumor development and to assess the signaling pathways via which exogenous melatonin counteract cancer growth. This goal has been achieved by novel approach for pineal destruction using dental micromotor which validated by melatonin downregulation in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Tumor growth tissues showed positive expression for survivin, while non-tumor tissues displayed little noticeable staining by immunohistochemistry [ 40 ]. Melatonin downregulated the expression of survivin to prevent cell growth, survival, and metastasis of solid tumors [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth tissues showed positive expression for survivin, while non-tumor tissues displayed little noticeable staining by immunohistochemistry [ 40 ]. Melatonin downregulated the expression of survivin to prevent cell growth, survival, and metastasis of solid tumors [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 B) is a pineal gland hormone regulating the sleep–wake cycle, gonadal activity, redox homeostasis, and immune functions 12 . It also has anti-tumor properties in different types of cancer, including breast, colorectal, pancreatic, endometrial, kidney, skin, and others 13 19 . Of note, melatonin lowers estrogen receptor expression, inhibits DNA replication, prevents metastasis, regulates angiogenesis, and apoptosis 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…An in vivo study demonstrated that, in adenocarcinoma, melatonin exerted abilities of regulating the interplay between forkhead box protein O1 (FoxO1), miR96, and miR215 signaling. This signaling axis may be a novel target for melatonin to diminish cancer cell growth, survival, and metastasis [ 49 ]. Melatonin can upregulate miRNA-34a/449a to promote apoptosis in colorectal cancer cells and a xenograft mouse model as well [ 50 ].…”
Section: Anticancer Effect Of Melatoninmentioning
confidence: 99%